Pengaruh Modal Intelektual Hijau dan Fleksibilitas Keuangan terhadap Keuangan Berkelanjutan - Putri Nuraeni Safitri; Etty Murwaningsari (LPPM POLITEKNIK LP3I BANDUNG, 2026)
This study aims to (1) examine the effect of green intellectual capital on sustainable finance and (2) examine the effect of financial flexibility on sustainable finance. Secondary data were used, comprising annual reports and sustainability reports of companies in the consumer non-cyclicals and basic materials sectors listed on the Indonesia Stock Exchange (IDX) for the period 2023–2024. Data were collected through purposive sampling, yielding 128 data samples that met the established criteria. This study employs a quantitative approach, with panel data regression analysis conducted using EViews 13. The results reveal that financial flexibility has a positive and significant effect on sustainable finance, indicating that optimal management of cash reserves and residual debt capacity enhances the company's ability to fund green investments and respond to stakeholder expectations without exposing itself to financial distress risk. In contrast, green intellectual capital shows no significant effect on sustainable finance, suggesting that the high initial investment required to develop environmentally oriented intangible assets prevents companies from realizing financial benefits in the short term. This study contributes to the development of literature on Resource-Based View (RBV) theory in the sustainability context and provides practical insights for companies and investors in leveraging internal funding flexibility as a crucial competitive advantage to support long-term business sustainability.